Effect of nitrogen forms and rates on yield and performance of young and mature cocoa trees in two agro-ecological zones in Ghana - Gyebi, Daniel Nana Yaw (University of Cape Coast, 2021)
A robust root system architecture (RSA) in interaction with increased antioxidant activities and osmoprotectants accumulation confer tolerance to crops when challenged by drought, resulting in improved yields. In addition to these innate plant mechanisms, various soil amendments, such as biochar, have also been proven to alleviate drought impacts on crops. Two experiments were conducted in this study. A greenhouse study was first conducted to assess genotypic variation in the RSA of 60 okra genotypes at the seedling stage. Based on the first experiment's results, ten genotypes from various clusters were selected for further screening under drought and biochar amendment in the 2nd experiment. In the 1st Experiment, genotypic variation was observed in all the RSA and biomass traits analysed. Genetic coefficient of variation (GCV) was high (>20%) for all biomass traits and the majority of RSA traits, barring lateral root angle and primary root length, which had low (60%) broad-sense heritability (H2) was recorded for all traits. Correlation analyses revealed a significant positive relationship between total root length and all other RSA traits. Population structure analysis through Ward’s hierarchical clustering grouped the genotypes into two clusters, with cluster 2 membership superior in most RSA traits. In the 2nd Experiment, drought elicited hyper-antioxidant (superoxide dismutase, ascorbic acid and salicylic acid) activities, increased osmoprotectants (proline and carbohydrate) and reduced pod yield (pod length, pod diameter, number of pods per plant and total pod yield). However, there were differential genotypic responses. Some genotypes recorded higher antioxidant and osmoprotectant contents, translating into higher yields. Biochar application mitigated the drought impact at increasing rates, evidenced by reduced antioxidants and osmoprotectants content, but increased pod yield. This study, therefore, demonstrated the presence of genetic diversity in the RSA of okra and the drought-mitigating potential of oil palm empty fruit bunch biochar on the biochemical and yield traits of okra. On the whole, cluster 2 genotypes (VI060692 and GH112) with superior RSA recorded greater overall antioxidant and osmoprotectants contents, and total pod yield, suggesting that RSA can be harnessed in selecting drought-tolerant okra genotypes.
xiv,139p.;ill
Keywords: Agro-Ecological Zones; Cocoa; Cocoa farms; Fertilizer application; Nitrogen-based fertilizers; Nitrogen Use Efficiency; Nitrogen Resorption